Alcohol consumption in young people between 18 and 24 years according to sociodemographic characteristics - Maria Belen Villace; Alicia Ruth Fernandez; Moacyr Lobo da Costa Junior (Universidade de São Paulo, 2013)
OBJECTIVE: to identify alcohol consumption in young people between 18 and 24 years of age in the province of Córdoba who participated in the National Survey of Risk Factors, according to sociodemographic characteristics. METHOD: a quantitative, analytic and cross-sectional study was undertaken in a sample of 240 young people. The alcohol consumption and sociodemographic characteristics were analyzed using bivariate analysis, risk ratio and confidence intervals. RESULTS: the lifetime prevalence of alcohol consumption corresponded to 79.17%, the one-year prevalence to 72.91% and the one-month prevalence to 57.08%, while episodic abuse and regular hazardous consumption corresponded to 25.55% and 24.19%. Consumption levels in the last month were higher among males (p=0.0028), single people (p=0.0001), with a secondary education degree (p=0.0306). CONCLUSION: in the province of Córdoba, drugs use, including alcohol, has not been an area of research interest in recent years, although alcohol abuse is associated with other risk factors, like accidents and violence, and is a factor of comorbidity and early mortality. Therefore, alcohol consumption in young people represents an area of concern and, once characterized, preventive actions should be adopted.